(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2024)
The City Resilience Index (CRI) is a key framework for assessing the resilience of cities to disasters and crises, thus contributing to the so-called "sustainability" and empowering of cities. It is an indicator that comprises four dimensions, including twelve goals, and fifty-two sub-indicators. The resilience of cities is built on ten qualitative indicators. These indicators fall within the four dimensions of the CRI – Health and Quality of Life, Economy and Society, Infrastructure and Ecosystems, and Leadership and Strategy. Therefore, the aim of this study is to examine the role of economic and social dimensions in enhancing the resilience of cities, within the concept of the Global Index of City Resilience, (CRI). The study showed a close correlation between the achievement of city resilience indicators and the socio-economic dimensions of cities, which was clearly reflected in the ability of cities to be economically and socially sustainable. This study showed the importance of indicators for preserving community identity and the importance of establishing interactive foundations between "strengthening institutional capacities for city resilience" and "community identity" for them, in order to enhance more sustainability and resilience of cities against internal or external migrations.